Kajian Medan Magnet Dan Pemanfaatannya Dalam Fisika Dasar - Alven Emanuel Harefa; Cindy Juwita Humendru (CV. SINAR HOWUHOWU, 2024)
The magnetic field is a fundamental concept in physics with significant roles in various natural phenomena and technological applications. This study aims to analyze the basic theory of magnetic fields, their applications in technology, and their impact on natural phenomena. Based on a literature review, it was found that the magnetic field is closely related to electromagnetic laws such as Ampère's and Faraday's laws, leading to practical applications such as electric motors, generators, and medical technologies like MRI. Additionally, Earth's magnetic field protects life from cosmic radiation and influences natural phenomena like the aurora. This study also highlights the role of magnetic fields in modern physics, particularly in particle physics experiments and quantum field theory. The findings emphasize the importance of understanding magnetic fields for technological development and scientific research in the future.